2005
DOI: 10.1152/ajpcell.00405.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of NBC1 in apical and basolateral HCO3 permeabilities and transendothelial HCO3 fluxes in bovine corneal endothelium

Abstract: Ϫ transport properties of the corneal endothelium. Recent work (13) suggested the presence of an apical 1Na ϩ -3HCO 3 Ϫ cotransporter (NBC1) in addition to a basolateral 1Na ϩ -2HCO 3 Ϫ cotransporter. We examined whether the NBC1 cotransporter contributes significantly to basolateral or apical HCO 3 Ϫ permeability and whether the cotransporter participates in transendothelial net HCO 3 Ϫ flux in cultured bovine corneal endothelium. NBC1 protein expression was reduced using small interfering RNA (siRNA). Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Recent studies (Diecke et al, 2004;Li et al, 2005) have confirmed that is secreted from the basolateral to apical side. This secretion is currently hypothesized to be the source of the ion-coupled osmotic fluid pumping.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent studies (Diecke et al, 2004;Li et al, 2005) have confirmed that is secreted from the basolateral to apical side. This secretion is currently hypothesized to be the source of the ion-coupled osmotic fluid pumping.…”
Section: Discussionmentioning
confidence: 86%
“…This secretion is currently hypothesized to be the source of the ion-coupled osmotic fluid pumping. Uptake of at the basolateral membrane is by co-transport via NBC1b (Li et al, 2005;Sun and Bonanno, 2003;Sun et al, 2000). Apical permeability however, is 3-4 times smaller than basolateral (Bonanno et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that siRNA knockdown of NBC significantly reduced basolateral HCO 3 -permeability and eliminated net basolateral to apical fluxes (Li et al 2005). Interestingly, studies using cultured cells indicate that basolateral HCO 3 -permeability is 3-4 times greater than apical permeability (Bonanno et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been used to explore the function of microsomal glutathione S-transferase 1 in protection of RPE cells from oxidative stress, 29 the effect of loss of mitochondrial DNA sequences on RPE cells, 30 the role of NeuroD in photoreceptor formation, 31 the role of stem cell factor/c-Kit in tumorigenesis of uveal melanocytes, 32 the role of aldehyde dehydrogenase isozymes or methionine sulfoxide reductase A in oxidative defense of lens cells, 33,34 the role of eukaryotic translation initiation factor 5A on tumor necrosis factora-induced apoptosis of lamina cribosa cells, 35 survivalpromoting effects of hepatocyte growth factor on corneal epithelial cells, 36 the role of 1Na + -3HCO 3 À cotransporter in HCO 3 À flux in corneal endothelial cells, 37 TGFb2-induced production of extracellular matrix by astrocytes derived from optic nerve, 38 and regulation of eye development by transcriptional control of CCCTC binding factor. 39 …”
mentioning
confidence: 99%